Methodologies to Improve the Mechanical Properties of Struc- tural Concrete with Recycled Aggregates (2014)
This paper presents the analysis of results about two methodologies proposed to reduce the differences of mechanical properties presented in recycled concrete made with high percentages of recycled aggregate in respect to a control concrete. Two methodolo